Audit committee independence, director ownership, audit quality and non-performing loans - Sen, Kanon Kumar; Abedin, Md. Thasinul; Hossain, Tanjila; Ghosh, Ratan (Penerbit Universiti Kebangsaan Malaysia, 2022)
The rising trend of Non-Performing Loans (NPLs) in the banking sector of Bangladesh epitomises a common phenomena of loan default that mostly arises from unwillingness to repay tendency of the borrowers who usually fit into the defined higher class of the society. An appropriate governance and control framework can effectively control this growing trend of NPLs, supplemented by the loan default culture. In view of this setting, this paper looks for the impact of audit committee independence, director ownership, external audit quality, CEO power, and bank size to control NPLs. After identifying two endogenous variables in a system of linear equations, this paper employs the system generalized method of moment (GMM) approach of regression analysis. This paper finds the significance of audit committee independence, director ownership, and external audit quality in controlling NPLs. However, this paper finds no significant impact of CEO power on lowering NPLs. Bank Size, measured in relative sense, has non-linear impact on NPLs. This paper recommends that the existing governance guidelines and BASEL-II accords fail to boost up the asset quality that controls NPLs and ensures capital adequacy.